The Prohibition of Khalwah in Hadith: A Ma‘ānī al-Ḥadīth Study and Its Relevance to the Regulation of Cohabitation under Article 412 of the 2023 Indonesian Penal Code - asep hikmatullah (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2026)
The ongoing phenomenon of cohabitation within society continues to ignite intense debates across moral, religious, and legal dimensions. While the state attempts to regulate cohabitative practices through Article 412 of the 2023 Indonesian Penal Code (KUHP), this provision has sparked widespread controversy, contrasting views that deem cohabitation a violation of religious and moral values against arguments that position it strictly within the realm of individual privacy. This study aims to analyze the prophetic tradition’s prohibition of khalwah (seclusion) using the ma‘ānī al-ḥadīth approach and to examine its relevance to the regulation of cohabitation under Article 412 of the 2023 KUHP. Employing a normative legal research method with a qualitative approach, this library-based study reveals that the prophetic prohibition of khalwah functions preventively to deter behaviors that could potentially lead to zinā (fornication/adultery). Furthermore, a normative alignment exists between the prohibition of khalwah and the cohabitation clause in the 2023 Penal Code, particularly regarding the safeguarding of public morality, decency, and the preservation of marriage and family institutions. Nevertheless, a distinct divergence in scope remains: the prohibition of khalwah operates as a preventive measure at the pre-action (potential) stage, whereas Article 412 of the KUHP penalizes cohabitation as an actualized conduct. This distinction illustrates a process of normative selection within national criminal law. The novelty of this research lies in its integration of the ma‘ānī al-ḥadīth approach to examine the prohibition of khalwah in direct relation to Article 412 of the new Indonesian Penal Code.